PENGARUH PENGEMBANGAN KARIR DAN PELATIHAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI PUSKESMAS ALAHAN PANJANG, KECAMATAN LEMBAH GUMANTI, KABUPATEN SOLOK - Andayani, Jihan Restu; Lusiana, Lusiana; Sopali, Mardhatila Fitri (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
This study aims to determine how much the influence of career development and job training on employee performance with job satisfaction as an intervening variable. The data analysis method used is the Structural Equation Model (SEM) method with the Partial Least Square (PLS) program. The method of data collection in this study was to use questionnaires filled out by respondents, namely 75 employees of the Alahan Panjang Health Center. From the results of this study shows that: (a) career development has a positive and significant effect on job satisfaction, (b) Job Training has a positive and significant effect on Job Satisfaction, (c) Career Development has a positive and insignificant effect on Employee Performance, (d) Job Training has a positive and insignificant effect on Employee Performance, (e) Job Satisfaction has a positive and significant effect on Employee Performance, (f) Job Satisfaction mediates Career Development on Performance Employees, (g) Job Satisfaction mediates Job Training on Employee Performance, (h) Career Development and Job Training Contribution by 40.7% to Job Satisfaction and (i) Career Development and Job Training Contribution by 55.3% to Employee Performance.